2018
DOI: 10.1371/journal.ppat.1007061
|View full text |Cite
|
Sign up to set email alerts
|

EcoHIV infection of mice establishes latent viral reservoirs in T cells and active viral reservoirs in macrophages that are sufficient for induction of neurocognitive impairment

Abstract: Suppression of HIV replication by antiretroviral therapy (ART) or host immunity can prevent AIDS but not other HIV-associated conditions including neurocognitive impairment (HIV-NCI). Pathogenesis in HIV-suppressed individuals has been attributed to reservoirs of latent-inducible virus in resting CD4+ T cells. Macrophages are persistently infected with HIV but their role as HIV reservoirs in vivo has not been fully explored. Here we show that infection of conventional mice with chimeric HIV, EcoHIV, reproduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(132 citation statements)
references
References 125 publications
(197 reference statements)
15
117
0
Order By: Relevance
“…We reported that prophylaxis with antiretrovirals prevented EcoHIV infection and the development of HIV–NCI in mice ( Gu et al, 2018 ). To test whether virus inhibited by poly I:C retains the ability to cause disease, the experiment shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that prophylaxis with antiretrovirals prevented EcoHIV infection and the development of HIV–NCI in mice ( Gu et al, 2018 ). To test whether virus inhibited by poly I:C retains the ability to cause disease, the experiment shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EcoHIV infects CD4 positive T cells and F4/80 positive macrophages systemically as well as brain microglia. After an early peak its replication is controlled, at least in part, by adaptive immune responses but chronically infected mice maintain some virus expression in macrophages and demonstrate impaired learning analogous to HIV-infected people on effective antiretroviral treatment ( Potash et al, 2005 ; Gu et al, 2018 ; Kelschenbach et al, 2019 ). The continued expression of HIV proteins in EcoHIV infected mice has allowed evaluation of vaccines to prevent infection and drugs to treat infection (Hadas et al, 2007; Im et al, 2011 ; Liu et al, 2018 ; Roshorm et al, 2009 , 2012 ; Saini et al, 2007 ; Tomusange et al, 2016a , 2016b ) and the persistence of HIV-associated neurocognitive impairment (HIV–NCI) in this model has allowed studies of some of the routes to pathogenesis and NCI treatment ( He et al, 2014 ; Kelschenbach et al, 2019 ; Bertrand et al, 2019 ; Jones et al, 2016 ; Kim et al, 2019 ; Nedelcovych et al, 2017 , 2019 ; Olson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…33 The EcoHIV model captures many aspects of HAND, for example, infection of T cells, macrophages and microglia, mucosal transmission of virus, normal CD4:CD8 ratio, a partially functional immune system, inflammatory responses in the brain, microgliosis, and neurocognitive impairment. 60,61 Numerous reports, including work from our laboratory, support the notion that this mouse model can be used as a versatile tool for characterizing potential anti-inflammatory therapeutics. 41,53,62 In this study, we utilized primary cultures of mouse glial cells exposed to EcoHIV which resulted in a significant increase in several inflammatory markers (ie, TNFα, IL-1β, IL-6, C3, CCL2, CCL3, and CXCL10) that have previously been reported to be implicated in the context of HAND.…”
Section: Discussionmentioning
confidence: 95%
“…EcoHIV Detectable viral load in the brain, neuroinflammation, loss of MAP-2 and synapsin II staining [179,337] Impaired working and spatial memory [179,181,182] Non-rodent animal models SIV infected macaques Depletion of CD4+ cells, detectable viral load in the brain, neuroinflammation, neuronal loss [162] Impaired performance in tasks assessing memory, fine/ general motor skills, motivation, reaction time, spatial working memory [338] FIV infected cats Encephalopathy, reduced peripherical and motor neuron conductance [206,207] Aggression, loss of socialization, gait changes [206,207] mice developed age-specific memory deficits and the model helped to delineate cellular pathways involved in gp120 mediated neurotoxicity [167,168]. Similarly, a Tat transgenic mouse model was also developed where Tat is expressed under the control of a doxycycline-dependent GFAP promoter, allowing for these mice to develop Tat-dependent brain pathologies such as astrogliosis, infiltration of monocytes/T-cells and premature death [169].…”
Section: Chimeric Virusesmentioning
confidence: 99%
“…This chimeric virus replaces gp120 with the murine leukemia virus gp80, facilitating entry into mouse cells [ 174 ]. Several studies have shown that mice infected with this chimeric strain display stable pro-virus in T-cells and macrophages, mucosal transmission of virus, normal CD4:CD8 ratios, a partially functional immune system and neurocognitive impairment [ 175 , 176 ]. Our group along with others has demonstrated that intracranial (IC) administration of EcoHIV at a dose of 1x10 6 pg p24 directly into the caudate putamen results in increased levels of several inflammatory genes [ 177 179 ].…”
Section: Animal Models Of Handmentioning
confidence: 99%